2000
DOI: 10.7326/0003-4819-133-11-200012050-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the QT Interval and Ventricular Tachycardia in Patients Treated with Arsenic Trioxide for Acute Promyelocytic Leukemia

Abstract: Cardiac toxicity occurs during arsenic trioxide therapy in patients with acute promyelocytic leukemia. Such patients should be monitored for prolonged QT intervals and ventricular arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(59 citation statements)
references
References 9 publications
1
58
0
Order By: Relevance
“…11,36,89 In a clinical trial, prolonged QT intervals (the time intervals for the contraction of the ventricle from the beginning of the Q wave to the end of T wave; a prolonged QT interval indicates cardiac toxicity) were observed in all patients during induction therapy with As 2 O 3 and ventricular premature contractions were noticed during eight of the twelve courses of therapy. 90 QT prolongation was also observed in 38% of patients in another clinical study. 89 The prolonged QT intervals could return to baseline following cessation of As 2 O 3 .…”
Section: Toxic Side Effects Of As 2 Omentioning
confidence: 85%
“…11,36,89 In a clinical trial, prolonged QT intervals (the time intervals for the contraction of the ventricle from the beginning of the Q wave to the end of T wave; a prolonged QT interval indicates cardiac toxicity) were observed in all patients during induction therapy with As 2 O 3 and ventricular premature contractions were noticed during eight of the twelve courses of therapy. 90 QT prolongation was also observed in 38% of patients in another clinical study. 89 The prolonged QT intervals could return to baseline following cessation of As 2 O 3 .…”
Section: Toxic Side Effects Of As 2 Omentioning
confidence: 85%
“…Animals exposed to arsenic at the dose of 1 mg/kg showed slight increase (nonsignificant) in resting HR (tachycardia) whereas high doses of arsenic (5 and 10 mg/kg) slowed down HR (bradycardia). There are several reports of serious life-threatening ventricular tachycardia on acute arsenic exposure (Lai et al 2005;Ohnishi et al 2000). Normally low blood pressure is regulated by increase in force of contraction of heart, to increase the stroke volume or the heart rate as a compensatory mechanism to maintain normal cardiac output that may be true in most reported cases of acute arsenic poisonings characterized with profound hypotension and tachycardia (Tortora and Grabowski 1993).…”
Section: Discussionmentioning
confidence: 97%
“…While four patients showed non-sustained VTs, one had TdP [96]. Ohnishi et al [97] also observed that all of the eight patients on ATO therapy developed QT prolongations, out of which four developed non-sustained VT. Similarly, in another multicentric ATO study in the USA, 63% of the patients showed QT prolongations but only one of them had an absolute QT interval of >500 ms together with an asymptomatic 7-beat run of TdP [98].…”
Section: Qt Prolongationmentioning
confidence: 91%